Problem-Based Learning Effects on Students Learning Outcomes in the Themes of The Potential and Utilization of Natural Resources - Syamsul Musthofa; Ketut Prasetyo; Nugroho Hari Purnomo (Universitas Negeri Surabaya, 2019)
This study aims to determine the effect of problem-based learning models on student learning outcomes. This study is Nonequivalent control group design. The sample in this study was class VII which was determined randomly. The material used is the potential and utilization of natural resources. The data obtained are then tested differently using the independent sample t-test. The results showed that the two research classes experienced positive changes regarding student learning outcomes. In the experimental class the problem-based learning model shows learning outcomes that are better than class controls. Calculation of the independent sample t-test posttest shows that students with Sig. (2-tailed) 0.019, where 0.019 <0.05 means that there is a significant difference. The existence of significant differences indicates that there is an influence of problem-based learning models on student learning outcomes.